Development of a Chemistry Magazine with Content Interpreting GC-MS Spectrum of Renggak Fruit Peel Extract as a Supplementary Resource for Organic Chemistry Lectures - Rahmawati, Rahmawati; Al Idrus, Syarifa Wahidah; Masruri, Baiq Laili Nisfi Siami (Jurnal Pijar Mipa, 2025)
Mastering the interpretation of spectra, as Gas Chromatography-Mass Spectrometry (GC-MS) spectra, in organic chemistry lectures for the analysis of natural materials is an important skill that often poses a challenge for students. This is especially true for natural materials in the surrounding environment that may have future potential, such as renggak fruits. This study aims to determine the results of interpreting renggak fruit peel extracts for use as content in a chemistry magazine, the level of validity, and student responses to the chemistry magazine developed as an alternative supplementary reading material. Conducted within the Chemistry Education Study Program at Mataram University, this study utilized the Research and Development (R&D) methodology, following the 4D model framework. The interpretation of the GC-MS spectrum of renggak fruit peel was carried out by matching the spectrum data obtained with the library data. The validity of the magazine was assessed using Aiken's V formula, while the reliability of the assessment was calculated based on the Percentage of Agreement (R) between validators. Student responses to the magazine product were obtained through a practical test. The results of the GC-MS spectrum interpretation of the renggak fruit peel extract showed the presence of the compounds myristic acid, palmitic acid, stearic acid, oleic acid, elaidinsaeure, heptadecene- (8)-carbonic acid-(1), 2-monoolein, 2-monopalmitin, ambretollide, 6-(2,6,6-Trimethyl-1-Cyclohexenyl)-4-Methyl-(E)-4-Hexen-1-ol, and cis-9-Octadecenal. The chemistry magazine product obtained an average Aiken's V validity score of 0.83, which falls into the “Highly Valid” category, with an average validator reliability score of 91%. The results of the chemistry magazine trial among 2021 Chemistry Education students obtained a practicality score of 92%, categorized as “Very Practical” as supplementary reading material. In the future, further exploration is needed regarding the content and design of the magazine to be created.